2022
DOI: 10.1097/sga.0000000000000600
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Endoscopic and Clinical Disease Activity With Fatigue in Inflammatory Bowel Disease

Abstract: f atigue is a common and debilitating symptom reported by patients with inflammatory bowel disease (IBD) (Borren, Long, Sandler, & ananthakrishnan, 2020). fatigue is defined as an overwhelming sense of tiredness, lack of energy, and feeling of exhaustion (Hulme et al., 2018), common among recently diagnosed patients (Grimstad et al., 2015) as well as those with long-standing disease (Huppertz-Hauss et al., 2017). Cross-sectional studies in persons with IBD have noted that fatigue is the most prevalent symptom,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…A study by Liu et al [21] found no statistically significant differences in CDAI scores among CD patients in different age groups. Similarly, a study by Kamp et al [22] on the correlation between disease activity and fatigue in inflammatory bowel disease patients did not find an impact of age. Although our study results differ from previous research, this discrepancy may be attributed to various factors, including sample size, study design, and differences in study populations.…”
Section: Relationship Between Age and Disease Activity In CD Particip...mentioning
confidence: 85%
“…A study by Liu et al [21] found no statistically significant differences in CDAI scores among CD patients in different age groups. Similarly, a study by Kamp et al [22] on the correlation between disease activity and fatigue in inflammatory bowel disease patients did not find an impact of age. Although our study results differ from previous research, this discrepancy may be attributed to various factors, including sample size, study design, and differences in study populations.…”
Section: Relationship Between Age and Disease Activity In CD Particip...mentioning
confidence: 85%
“…Based on published literature and our prior work in chronic pain populations, morning light treatment has the potential to improve not only mood and sleep in IBD, but also improve gastrointestinal symptoms and possibly even intestinal inflammation. Even if morning light treatment were to only improve mood and sleep in patients with IBD, this treatment would assist at least 50% of IBD patients who suffer from such symptoms [4][5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with IBD suffer from relapsing and remitting flares with gastrointestinal symptoms such as diarrhea, rectal bleeding, and abdominal pain as well as extraintestinal symptoms such as sleep and mood disturbances [3]. In fact, an estimated 56% of IBD patients report poor sleep quality [4] and mood disorders such as depression affects at least 20-30% of patients with IBD [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%